Airglow imaging observations of smallâ€ scale structures driven by convective instability in the upper mesosphere over Tirunelveli (8.7Â°N) - Narayanan, V. Lakshmi; Gurubaran, S.; Emperumal, K. (My University, 2010)
Airglow imaging observations of broadband OH Meinel band emissions made on the night of 20 January 2007 from the tropical Indian site Tirunelveli (8.7Â°N, 77.8Â°E) reveal largeâ€ and smallâ€ scale wave features that are aligned perpendicular to each other and that are associated with gravity wave dynamics. The largeâ€ scale waves were the signatures of propagating quasiâ€ monochromatic (QM) waves, whereas the smallâ€ scale features were identified to be ripples generated by convective instability in the mesosphereâ€ lower thermosphere (MLT) region. The QM waves showed consistent propagation toward the northwest direction throughout the observation period of âˆ¼4.5 hr, whereas the ripples that manifested as shortâ€ lived patches in the airglow images were transient and did not show any prominent phase propagation. In addition to these wellâ€ resolved structures in images, we infer the presence of waves with relatively longer observed time periods (compared with the observed time period of QM waves) from the spectrum of the time series generated with zenith intensity values derived from the images. From the complementary wind and temperature data obtained with coâ€ located MF radar and Sounding of Atmosphere with Broad band Emission Radiometry on the Thermosphere Ionosphere Mesosphere Energetics and Dynamics mission, an attempt is made to understand the dynamic processes occurring in the vicinity of the mesopause during the night of 20 January 2007. The uniqueness of the present observations is that there were shortâ€ lived ripple patches seen in various parts of the sky during the entire observation period of 4.5 hr. The precipitation rates obtained by the Tropical Rainfall Measuring Mission satellite mission suggest that the deep convective activity occurring over the equatorial eastern Indian Ocean provided a plausible source mechanism for sustained generation of the waves observed over Tirunelveli during this night.
Keywords: Airglow imaginh; Upper Mesosphere; Mesosphere; Tirunelveli; Tropical Area; OH Meinel band; Quasi-monochromatic waves; MLT region